The Problem of Industrial Localization in Egypt - Hassan, Abdel-Aziz Hassan (INP, 2025)
The study addresses the phenomenon of industrial localization, analyzing the factors explaining the concentration of industrial investments in specific regions and the resulting challenges in achieving regional balance and national development goals. The study indicates that the geographical distribution of industrial investments was uneven, with industries concentrated in major urban areas due to the availability of infrastructure, markets, and a trained workforce, while peripheral regions remained less affected by these investments. It also demonstrates that other industrial policies, such as support for consumer industries or encouraging foreign direct investment, have contributed to strengthening this concentration rather than addressing it. From an economic perspective, considerations of efficiency and cost minimization played a decisive role, as firms tended to locate near ports, transport hubs, and areas with high consumer demand. However, this process intensified regional disparities, widening the development gap between urban-industrial cores and less developed rural or peripheral areas. The study concludes that addressing the problem of industrial localization requires comprehensive regional planning policies, including incentives for investment in disadvantaged regions, integrated infrastructure development, and industrial strategies aimed at achieving equitable spatial distribution of growth in line with national development goals.